Associations between white matter hyperintensities, striatal dopamine loss, and cognition in drug-naïve Parkinson's disease. (April 2022) - Jeong, Seong Ho; Lee, Hye Sun; Jung, Jin Ho; Baik, Kyoungwon; Sohn, Young H.; Chung, Seok Jong; Lee, Phil Hyu
Abstract: Introduction: This study investigated the relationship between white matter hyperintensities (WMHs), nigrostriatal dopamine deficits, and cognitive decline in patients with drug-naïve early-stage Parkinson's disease (PD). Method: This cross-sectional study enrolled 309 non-demented patients with de novo PD who underwent [ 18 F] N-(3-fluoropropyl)-2β-carbonethoxy-3β-(4-iodophenyl) nortropane positron emission tomography, brain magnetic resonance imaging, and a detailed neuropsychological test at baseline. We quantified dopamine transporter (DAT) availability in each striatal sub-region and applied the Scheltens scale to assess the severity of periventricular and deep WMHs. The relationships between WMHs, DAT availability, and cognition in PD were assessed using multivariate linear regression and mediation analyses while adjusting for age at parkinsonian symptom onset, sex, disease duration, and vascular risk factors. Results: The severities of periventricular and frontal WMHs were associated with striatal DAT availability. Periventricular WMHs affected the level of cognitive performance in all cognitive domains, while frontal WMHs affected the attention/working memory and frontal/executive function domains. The effects of WMHs on attention/working memory and frontal/executive dysfunction were mostly direct with minimal mediating effects through striatal DAT availability. Meanwhile, striatal DAT availability fully mediated the association between WMHs and cognitive impairment in the visuospatial and memory function domains. Conclusion: This study demonstrated the different effects of WMHs on cognitive impairment depending on the cognitive domains in PD. These findings suggest a close link between comorbid WMHs, striatal dopamine depletion, and cognition in patients with PD. Highlights: White matter hyperintensities (WMHs) significantly affect cognitive impairment in patients with Parkinson's disease (PD). The effects of WMHs on cognitive impairment differs depending on the cognitive domains in PD. This study suggests a close link between comorbid WMHs, striatal dopamine depletion, and cognition in patients with PD.